Association of periodontal disease with migraine: A large‐scale community‐based cross‐sectional study. Issue 4 (10th April 2023) - Chen, Yen‐Ju; Hu, Kai‐Fang; Chan, Chi; Huang, Claire; Huang, Yu‐Han; Wang, Yen‐Feng; Wang, Shuu‐Jiun; Chen, Shih‐Pin; Lee, Mei‐Hsuan
Abstract: Background: Periodontal disease may drive a systemic inflammatory response that triggers migraine; however, the association between periodontal disease and migraine has rarely been investigated in a community‐based setting. Methods: This cross‐sectional study included 66, 109 participants aged 30 to 70 years from Taiwan Biobank (TWB). A structured questionnaire was administered to participants, who were also subjected to whole‐genome single nucleotide polymorphism genotyping using the customized Axiom–TWB array. To identify subjects with periodontal disease and migraine, the computerized linkage of data obtained from TWB and the National Health Insurance Research Database was performed. Participants were evaluated for their genetic predisposition to migraine using a polygenic risk score. We examined and estimated the magnitude of associations between periodontal disease and migraine. Results: In this study, 4618 (4618/66, 109; 7%) participants with migraine and 61, 491 (61, 491/66, 109; 83%) participants without migraine were included. Participants with migraine exhibited a higher prevalence of periodontal disease than participants without migraine (4324/4618; 94% vs. 56, 036/61, 491; 91%). A significant positive association was observed between periodontal disease and migraine, with an adjusted odds ratio (ORadj ) of 1.40 (95% confidence interval [CI] = 1.24–1.59; p <  0.001). The association remained consistent even after excluding participants with other comorbidities (ORadj  = 1.34; 95% CI = 1.16–1.55; p <  0.001). Moreover, the positive association between periodontal disease and migraine remained significant across the subgroups of age, sex, other comorbidities, and classified polygenic risk scores of migraine, with the ORadj ranging from 1.26 to 1.78. Conclusions: A significant positive association was observed between periodontal disease and migraine. Future studies need to explore the biological mechanisms of how periodontal disease might affect migraine.